Politik etis dan priayi baru: mobilitas masyarakat di Pulau Jawa 1900-1942 - Jati Saputra Nuriansyah; Ahmad S. Paramasatya; Reo Rafienza (Historiography: Journal of Indonesian History and Education, 2023)
This writing is motivated by the ethical political policy enacted by the Dutch Colonial government in Java.  The methods used in this research include topic selection, heuristics, verification, interpretation, and historiography. The result of the discussion of this article is that the new priayi in Java was caused by ethical politics implemented by the Dutch, allowing people to mobilize social status. Social status mobility through education became commonplace for ordinary people and its existence threatened the lives of the pangreh praja or old priayi. The objectives of writing this article are 1) To describe the classification of the population on the island of Java; 2) To know the government and ethical politics in Java; and 3) To describe the emergence of new priayi in Java.Penulisan ini dilatarbelakangi oleh kebijakan politik etis yang diberlakukan oleh pemerintah Kolonial Belanda di Pulau Jawa.  Metode  yang  digunakan  dalam  penelitian  ini  meliputi  pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi. Hasil dari pembahasan artikel ini yaitu priayi baru di Jawa diakibatkan oleh politik etis yang diterapkan oleh Belanda sehingga memungkinkan masyarakat untuk bermobilisasi status sosial. Mobilitas status sosial melalui jalur pendidikan menjadi hal yang lumrah bagi masyarakat biasa dan keberadaannya mengancam kehidupan para pangreh praja atau priayi  Adapun tujuan dari penulisan artikel ini yaitu 1) Untuk mendeskripsikan klasifikasi penduduk di Pulau Jawa; 2) Untuk mengetahui pemerintahan dan politik etis di Jawa; dan 3) Untuk menjabarkan kemunculan priayi baru di Pulau Jawa.